CRISPR/Cas9‐mediated MSTN disruption and heritable mutagenesis in goats causes increased body mass. (14th February 2018) - Wang, X.; Niu, Y.; Zhou, J.; Zhu, H.; Ma, B.; Yu, H.; Yan, H.; Hua, J.; Huang, X.; Qu, L.; Chen, Y.
Summary: Genetic engineering in livestock has been greatly enhanced through the use of artificial programmed nucleases such as the recently emerged clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated 9 (Cas9) system. We recently reported our successful application of the CRISPR/Cas9 system to engineer the goat genome through micro‐injection of Cas9 mRNA and sgRNAs targeting MSTN and FGF5 in goat embryos. The phenotypes induced by edited loss‐of‐function mutations of MSTN remain to be evaluated extensively. We demonstrate the utility of this approach by disrupting MSTN, resulting in enhanced body weight and larger muscle fiber size in Cas9‐mediated gene‐modified goats. The effects of genome modifications were further characterized by H&E staining, quantitative PCR, Western blotting and immunofluorescence staining. Morphological and genetic analyses indicated the occurrence of phenotypic and genotypic modifications. We further provide sufficient evidence, including breeding data, to demonstrate the transmission of the knockout alleles through the germline. By phenotypic and genotypic characterization, we demonstrated the merit of using the CRISPR/Cas9 approach for establishing genetically modified livestock with an enhanced production trait.